APPLICATION INTERACTIVE TOURISM OF BANDA ACEH CITY USING ADOBE FLASH CS6 - Farhansyah, Atras; Muttaqin, Muttaqin (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2016)
Development of multimedia makes the delivery of information becomesmore practical. Banda Aceh is a city that has tourism potential which is arelic of history. The problem is the media to promote the tourist attractionsand historic sites is not maximized. For that created an interactiveapplication that contains information on tourism in the city of Banda Aceh.In scientific writing, create interactive applications Banda Aceh tourismusing Adobe Flash CS6. This application is interactive in which the usercan choose the location where you want to know. The interactiveapplication is also accompanied by a minimalist travel map containingtourist sites. It also added amenities of the town and a glimpse ofinformation contains the address of the tourist attractions. Output is later isa file-based application exe (Execute) file and swf (Small Web Format)files which contains information on tourism sites in Banda Aceh. Output ofthe file will be saved in the long term and more practical. This application isexpected to be used by the people of Banda Aceh to promote touristplaces in the city. With the media is also expected to foster communityinterest outside Banda Aceh to visit attractions in the city of Banda Aceh.Keyword : Media Information, Tourism, Multimedia, InteractiveApplication.